Active Learning in STEM Education with Regard to the Development of Inquiry Skills - Zuzana Ješková; Stanislav Lukáč; Ľubomír Šnajder; Ján Guniš; Daniel Klein; Marián Kireš (MDPI AG, 2022)
Active learning, represented by inquiry-based science education (IBSE) strategies, is considered essential for students to develop skills and knowledge to prepare for the challenges of the 21st century world. The success of IBSE, and the resulting development of inquiry skills in particular, can be enhanced by various factors. This study is focused on the synergetic effect of the implementation of IBSE through well-designed inquiry activities across STEM-related disciplines, enhanced by digital technologies and formative assessment tools, delivered by teachers educated in this field. The corresponding research based on a quasi-experimental design evaluated the effect on the development of inquiry skills that were identified before and after a period of consistent implementation of IBSE, using a written test of inquiry skills as the main research instrument. The research findings on the sample of 2307 upper secondary school students confirmed a low initial level of inquiry skills, however a statistically significant improvement in students' inquiry skills with medium size effect was identified. The detailed analysis shows the largest impact in the skill of determination of accuracy and statistically significant differences between genders without practical importance, however no difference was identified with regard to the number of inquiry activities undertaken.